Indonesia : Managing Decentralization - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 2002)
The process of decentralization in Indonesia was initiated after a long period of autocratic rule. Despite the political imperatives, there is a need to carefully sequence the fiscal decentralization to ensure that financing follows the assignment of functions. The functions should be commensurate with the capacity to provide public services. The paper argues for the proper sequencing to avoid jeopardizing macroeconomic stability or the effective delivery of public services.